Decoding lymph nodes: The crucial role of cytopathologists in diagnosing possible lymphoma - Udit K Naik; Y. Helen Zhang (Elsevier, 2024)
Cytopathologists have assumed a progressively pivotal role in diagnosing lymphoproliferative disorders. This review outlines a concise approach to the work-up of suspected lymphoma in cytopathology practice, emphasizing the integration of cytomorphologic evaluation with ancillary studies. These include the application of rapid onsite evaluation (ROSE) for proper specimen triage, immunophenotyping through flow cytometry (FC) and immunohistochemistry (IHC), and molecular studies on cytology/small biopsy specimens. Furthermore, the review provides a brief introduction to the forthcoming WHO Reporting System in Lymph Node Cytopathology.